Pregnancy in Disability: Community Perceptions and Personal Experiences in a Rural Setting in Ghana - Bridget Dela Akasreku; Helen Habib; Augustine Ankomah (Journal of Pregnancy)
Background. Persons with disabilities (PWDs) generally face strong discrimination and exclusion, especially with regard to their sexual and reproductive health. There is a prevailing social myth in Ghana that women with disabilities are asexual and cannot experience a positive motherhood experience. Although the World Health Organization recommends that research is conducted in this regard, community attitudes towards pregnant women living with disabilities remain largely unexplored. The purpose of this study was to explore community attitudes to pregnancy among women living with disabilities. Methodology. The study design was a mixed method cross-sectional study involving quantitative face-to-face individual interviews with 400 randomly selected community members (both males and females) in three communities in the Adaklu District of Volta Region in Ghana. In addition, in-depth interviews were held with five female PWDs. Simple and multiple logistic regression analysis were used to examine the factors associated with perceptions towards pregnant PWDs. Results. Majority of respondents agreed that pregnant women with disabilities should be kept in special institutions until delivery to prevent transmission of their disability to fetuses of pregnant women without disabilities. People also believed that pregnant PWDs are incapable of a safe motherhood experience. Among the strongly influencing factors for negative attitudes towards pregnancy of PWDs were educational status (p<0.001) and perceptions that the disability is caused by accidents (p<0.001) or spiritual issues (p<0.01). Regarding the relationship between perceived cause of disability and the resultant attitudes, respondents were three times more likely to have negative attitude and perceptions towards pregnant women with disabilities if their causes of disabilities were perceived to be spiritual compared to the cause being medical. Conclusion. Our findings indicate that there are generally negative societal attitudes towards pregnant PWDs. The evidence suggests that a degree of prejudice and misconceptions exists towards the pregnancy of women living with disabilities. Generally, there is a public perception that women living with disabilities cannot have a safe motherhood experience and are capable of transferring their disability to an unborn child of another pregnant woman.